Changing disturbance regimes, ecological memory, and forest resilience. Issue 7 (September 2016) - Johnstone, Jill F; Allen, Craig D; Franklin, Jerry F; Frelich, Lee E; Harvey, Brian J; Higuera, Philip E; Mack, Michelle C; Meentemeyer, Ross K; Metz, Margaret R; Perry, George LW; Schoennagel, Tania; Turner, Monica G
Abstract : Ecological memory is central to how ecosystems respond to disturbance and is maintained by two types of legacies – information and material. Species life‐history traits represent an adaptive response to disturbance and are an information legacy; in contrast, the abiotic and biotic structures (such as seeds or nutrients) produced by single disturbance events are material legacies. Disturbance characteristics that support or maintain these legacies enhance ecological resilience and maintain a "safe operating space" for ecosystem recovery. However, legacies can be lost or diminished as disturbance regimes and environmental conditions change, generating a "resilience debt" that manifests only after the system is disturbed. Strong effects of ecological memory on post‐disturbance dynamics imply that contingencies (effects that cannot be predicted with certainty) of individual disturbances, interactions among disturbances, and climate variability combine to affect ecosystem resilience. We illustrate these concepts and introduce a novel ecosystem resilience framework with examples of forest disturbances, primarily from North America. Identifying legacies that support resilience in a particular ecosystem can help scientists and resource managers anticipate when disturbances may trigger abrupt shifts in forest ecosystems, and when forests are likely to be resilient.